Bibliography: terrorism Research Literature : (Part 4) - Tinnes, Judith (Perspectives on terrorism, 2022)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, and grey literature on the field of Terrorism Research, its sub-disciplines (such as Critical Terrorism Studies), and related disciplines (such as Security Studies), central concepts, theories, methods, models, approaches, frameworks, and research topics. It focuses on recent publications (up to September 2022) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.